Improving Students’ Grammar through Socrative Application in Vocational High School in Central Java - Tiara Marcella Prasetyo; Issy Yuliasri (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the effect of the Socrative application on improving their grammar and motivation in English learning. The subject of this research is an 11th-grade vocational high school with a major in Pharmacy, which will participate in a three-month program using the Socrative application. The Socrative is used to help student master their grammar skills. The purpose of this study is to investigate how the Socrative application, used as a teaching medium, enhances the mastery of grammar, improves motivation in learning grammar, and how students perceive its use in teaching grammar. This research utilizes dynamic assessment to support students in learning grammar. This study uses a quasi-experimental design and a closed questionnaire for gathering data. the one that participate the. The collected data were then analyzed quantitatively using SPSS. The results indicate that Socrative effectively improved students’ reading comprehension. The students reported that Socrative created a new and more engaging learning atmosphere during the activities. The average for the pre-test is 77.84, while the average for the post-test is 91.73. The average from the subtraction of the posttest with pretest is 13.88. It can be deduced and summarized that using Socrative as the teaching medium indeed manages to help improve the grammar mastery of the students. The mean difference between pre-test and post-test scores was −13.88, showing a substantial increase in grammar mastery after the intervention. The obtained t value of −4.94 with 16 degrees of freedom and a significance value below 0.001 indicates that the difference was statistically significant